An evaluation model for children's foot & ankle deformity severity using sparse multi-objective feature selection algorithm. (December 2022) - Pan, Xiaotian; Zhang, Guodao; Lin, Aiju; Guan, Xiaochun; Chen, PingKuo; Ge, Yisu; Chen, Xin
Abstract: Foot & ankle deformity is a chronic disease with high incidence and is best treated in childhood. However, the current diagnostic procedures rely on doctor's consultation and empirical judgment, and lack objective and quantitative evaluation methods, resulting in low screening rates. To solve this problem, this paper aims to construct an evaluation model for children's foot & ankle deformity through data mining and machine learning technologies. Firstly, it proposes the grading rules for children's foot & ankle deformity severity based on analyzing the existing quantitative indexes and expert experience. Then the 3D foot scanner is used to collect the sample data including 30 foot structure indexes. Finally, an advanced sparse multi-objective evolutionary algorithm (sparse MO-FS) is present for feature selection. The effectiveness of the proposed sparse MO-FS and its search efficiency are proved by comparing 8 feature selection methods and 7 search strategies. Using sparse MO-FS, foot length, arch index, ankle index, and hallux valgus index are selected, which not only simplifies the evaluation model but also improves the average classification accuracy of random forest to more than 98%. Highlights: A grading rules of the severity of children's foot & ankle deformity are proposed. An advanced sparse multi-objective feature selection method is presented. An evaluation model for children's foot & ankle deformity severity is constructed. The model can be used for the 3D foot scanner to generate an evaluation result.